SENAM DISMENOR MENURUNKAN NYERI DISMENOR PADA REMAJA - Sugiharti, Rosi Kurnia; Amelia, Amelia; Sudrajat, Ananda Dwi Liandy (Jurnal Delima Harapan, 2025)
Background: Dismenore is a pain or discomfort in the lower abdomen felt by women before, during menstruation. There are two ways to relieve dysmenorrhea pain, first therapy by taking medication and second therapy without taking medication. Therapy without taking drugs can be by relaxing and exercising dysmenorrhea gymnastics. Dysmenore exercise can provide comfort to muscles around the waist, stomach, and pelvis. If done continuously in an orderly manner, it can also cause a gradual feeling of comfort. Objective: To identify the effect of dysmenorrhea gymnastics on dysmenorrhea pain in teenage girls at MTS Alwathoniyah 55 Karang Bahagia. Method: Applying a quantitative method and using a quasi experimental one group pretest-postest design. The subjects of this study were 30 respondents who suffered from dysmenorrhea. Results: Based on research findings, the average age of respondents was 14. The majority of respondents experienced pain before moderate intensity with a percentage of 60%, meanwhile, in the after measurement, generally respondents received a decrease in dysmenorrhea to mild pain with a percentage of 70%, furthermore, there was an increase in the number of respondents who did not feel pain with a percentage of 20% from 0%. Based on Wilcoxon's research, a value of = 0.000 (p<0.05) means that there is an effect of dysmenorrhea on the reduction of dysmenorrhea pain. It is expected that women are being dismenorrhea to do light exercise to reduce dysmenorrhea.